2004
DOI: 10.1111/j.1523-1755.2004.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin blocks multiple sites of the TGF-β signaling cascade in renal cells

Abstract: Curcumin blocks TGF-beta's profibrotic actions on renal fibroblasts through down-regulation of TbetaRII, and through partial inhibition of c-jun activity. These in vitro data suggest that curcumin might be an effective antifibrotic drug in the treatment of chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
108
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(116 citation statements)
references
References 28 publications
6
108
0
2
Order By: Relevance
“…PAI-1 can be induced by TGF-␤1 in rodent kidneys and in cultured mesangial cells. 22,23 TGF-␤1 transgenic mice developed expanded ECM, which was accompanied by increased levels of PAI-1 in vivo. 22 We previously reported upregulation of TGF-␤1 mRNA in glomeruli by ISH that parallels the accumulation of ECM proteins in TSLP mice 24 and now show that this correlates with upregulated PAI-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…PAI-1 can be induced by TGF-␤1 in rodent kidneys and in cultured mesangial cells. 22,23 TGF-␤1 transgenic mice developed expanded ECM, which was accompanied by increased levels of PAI-1 in vivo. 22 We previously reported upregulation of TGF-␤1 mRNA in glomeruli by ISH that parallels the accumulation of ECM proteins in TSLP mice 24 and now show that this correlates with upregulated PAI-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…14,18,20) Likewise, rapamycin reduced fibrosis and attenuated disease progression in rat models of liver cirrhosis and pulmonary fibrosis. 21,22) Therefore, these data suggest that TGF-β1 contributes to EMT by activating the Akt/mTOR pathway, and the inhibition of this pathway can restrain organ fibrosis.…”
Section: Curcumin Suppresses Epithelial-mesenchymal Transition Of Renmentioning
confidence: 99%
“…Although it is reported that curcumin can block the TGF-β signaling cascade at multiple sites in renal cells, 22) it is still largely unknown whether the Akt/mTOR signaling pathway is involved in the curcumin-induced anti-fibrotic effect. Therefore, we presume that curcumin prevents TGF-β1-induced EMT through the inhibition of the AKt/mTOR signaling pathway.…”
Section: Curcumin Suppresses Epithelial-mesenchymal Transition Of Renmentioning
confidence: 99%
See 1 more Smart Citation
“…Este efecto es producido por el metabolismo del CCl 4 que causa la peroxidación lipídica y la producción de los radicales libres (33) , conduciendo a la disfunción de los mismos, la liberación de ROS, y mediadores fibrogénicos e inflamatorios. Tras la lesión en el hígado, las células hepáticas producen colágeno fibrilar dentro del tejido dañado (34) , induciendo la inflamación, promoviendo la progresión de la fibrogénesis hepática y causando la necrosis de los hepatocitos (35) . El extracto acuoso liofilizado de C. longa 200 mg, mejoró los cambios patológicos producidos por CCl 4 , mostrando un parénquima hepático normal hacia la normalización de las funciones celulares y restauración de los niveles séricos de AST, ALT y ALP.…”
Section: Discussionunclassified